A new data hiding technique based on irreducible polynomials - Abduallah, Wafaa Mustafa; Rahma, Abdul Monem S.; Pathan, Al-Sakib Khan (Academy Publisher, Finland, 2013)
The mass diffusion of digital communication needs the special means of security. Cryptography concentrates on rendering the messages unreadable to any unauthorized person who might intercept those. In contrast, steganography is a method of concealing the existence of message to allow a secure communication in a complete undetectable manner. Digital image is the most common type of carrier used for steganography. This paper presents a new method for data hiding within transform domain of the color images which is based on dividing the image into blocks, then applying the proposed transform on specified blocks and hiding the secret message within them. In this way, the security can be increased since it depends on a different type of transform which is based on irreducible polynomial mathematics. According to our investigation in this area, our work for the first time uses this mechanism for data hiding. The results have proven increasing the capacity with maintaining reasonable level of imperceptibility.